2008
DOI: 10.1021/ci600383v
|View full text |Cite
|
Sign up to set email alerts
|

Sharing Chemical Information without Sharing Chemical Structure

Abstract: Studies to assess the risks of revealing chemical structures by sharing various chemical descriptor data are presented. Descriptors examined include "Lipinski-like" properties, 2D-BCUT descriptors, and a high-dimensional "fingerprint-like" descriptor (MACCs-vector). We demonstrate that unless sufficient precautions are taken, de novo design software such as EA-Inventor is able to derive a unique chemical structure or a set of closely related analogs from some commonly used descriptors. Based on the results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…It remains to be seen how well the descriptors used mask the structure identity, and further studies will be required for assessment of this factor, such as that performed with other descriptors (Masek et al, 2008). We have not described the actual sharing of models or the format, for doing this will require testing to ensure compatibility and reproducibility among laboratories.…”
Section: Downloaded Frommentioning
confidence: 99%
See 2 more Smart Citations
“…It remains to be seen how well the descriptors used mask the structure identity, and further studies will be required for assessment of this factor, such as that performed with other descriptors (Masek et al, 2008). We have not described the actual sharing of models or the format, for doing this will require testing to ensure compatibility and reproducibility among laboratories.…”
Section: Downloaded Frommentioning
confidence: 99%
“…These data would represent precompetitive data, and we would need to ensure that molecular structures could not be distinguished or reverseengineered from the training sets and descriptors upon which the models were built (Masek et al, 2008). ADME/Tox programs have been traditionally limited in using the same very small datasets from the literature or combining datasets from different groups.…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…It has not been conclusively proven that such a “one-way” descriptor can be defined. For example Masek et al [63] have shown that one can regenerate a target structure (or substructural features) or a set of closely related analogs given a combination of descriptors such as BCUTs. Tetko et al [64] suggest an approach to prevent reverse engineering but avoid the use of descriptors and instead sharing structures of related molecules, rather than the molecules of interest.…”
Section: What Is a Useful Descriptor?mentioning
confidence: 99%
“…For example, the Burden-CAS-University of Texas (BCUT) descriptors [78] are eigenvalues of the atomic property-weighted Burden matrix [11]. Linking the eigenvalues back to the molecular structure can be a difficult task, though Masek et al [70] have recently shown that one could derive connection tables from the values of a set of BCUT descriptors. Though this can be considered one form of interpretability, it is indirect and more challenging than descriptors with a clear physical connection to molecular structure.…”
Section: Descriptorsmentioning
confidence: 99%